Tax reforms in developing countries - Karl Wolfgang Menck (Intereconomics, 1992)
Given the low level of tax revenue and the contradictory structure of tax legislation in many developing countries, there is broad agreement on the need for tax reforms in those countries. The following article reviews the problems associated with instituting such changes.
Keywords: 330